Da Carta à rainha louca ao Mar de rosas: o presentemente feminino e os desafios da história - Soares, Deivanira Vasconcelos (2023)
The relationship between women and the time of their existence in fiction, with a historical background from the 18th century, is the reflexive impulse of this study, which is mainly based on the denouncing voice/writing of Isabel, a character in the epistolary novel Carta à Rainha louca (2019), by Maria Valéria Rezende. To establish an intertemporal and interartistic comparison, representative of this era of image, we chose Felicidade, from the film Mar de rosas (1977), by Ana Carolina, to demarcate, chronologically, possibilities of approximations and/or distances between the characters and fictional/historical events read. from the perspective of being a woman in the world. The theoretical problem that the thesis answers involves the limited relationship of the effect of tripartite time on these women and the elaboration of their self-awareness of being in the “patriarchal here and now”. We currently call this the time for a conscious alert indicating that the “object women” of a context by force of the established world order are the same actors, agents of change necessary for an experience beyond traditionalist repetition. Our methodology is critical and comparative analysis woven in order to understand the characters and their afflictions in dealing with temporality. We analyze the writings and voices in the epistle and in the film, observing the fictional developments of the narration of their existence in light of the conceptions of time and the work of this other, presently. With this intention, we reflect on the relationship between woman/narrative time and woman/historical time, moving through this cultural discursive set to understand the action of the scene and its symbolic mediations because it is from historical time that the time of action is borrowed. The theoretical basis that underpins time in research discusses, from the perspective of contemporary feminist criticism, contributions from Paul Ricoeur (2010), Gilles Deleuze (2012; 2021), Giorgio Agamben (2021), and others; on the bridge for the necessary historical, social and political discussion that the novel demands, we look for Mary del Priore (2019; 2020), Liana Reis (1989), Flávia Biroli (2014), Carla Akotirene (2020), Virgínia Woolf (2019), Pierre Bourdieu (2018), and Sueli Carneiro (2011).